Unveiling the benefits of Vitamin D3 with SGLT‑2 inhibitors for hypertensive obese obstructive sleep apnea patients - Huai Heng, Loh; Siow Phing, Tay; Ai Jiun, Koa; Mei Ching, Yong; Asri, Said; Chee Shee, Chai; Natasya Marliana, Abdul Malik; Anselm, Su Ting; Bonnie Bao Chee, Tang; Florence Hui Sieng, Tan; Norlela, Sukor (BioMed Central Ltd, 2025)
Background Obstructive sleep apnea (OSA) is associated with poorer quality of life (QoL) and increased cardiovascular risks, which may be exacerbated by hypovitaminosis D. Sodium glucose transporter-2 inhibitor (SGLT2i) provides cardiovascular benefits beyond glycemic control. As vitamin D3 and SGLT2i act through different pathways with similar mechanisms in improving cardio-metabolic health, this study aimed to investigate the synergistic effects of this combination therapy in improving these parameters and QoL in hypertensive obese OSA patients. Methods Patients who fulfilled the study criteria were randomized to receive: (i) Dapagliflozin, (ii) vitamin D3, (iii) Dapagliflozin plus vitamin D3, or (iv) no treatment, for 16 weeks. The parameters evaluated included anthropometric measurements, uric acid, HbA1c, lipid profile, steatotic liver disease grade, plasma aldosterone concentration, plasma renin concentration, ultrasound flow-mediated dilatation of brachial artery, hsCRP, heart rate variability (HRV), Epworth Sleepiness Scale (ESS), and QoL scores. Results A total of 163 patients were recruited and 153 completed the study. The combination of vitamin D3 and Dapagliflozin treatment led to significant improvements in metabolic parameters and nocturnal heart rates, and prevented deterioration of HRV, with healthier HRV at the end of study visit compared to the control group. Only the combination group exhibited improvements in both ESS and QoL scores. Conclusions This is the first study to demonstrate beneficial effects of combining vitamin D3 and SGLT2i in cardiometabolic outcomes and QoL in hypertensive obese OSA patients. These findings highlight the potential of this combination therapy in addressing the cardio-metabolic challenges and QoL in this patient population. Trials registration NCT06690723. Registered 10 October 2024—Retrospectively registered, https://register.clinicaltr ials.gov/prs/beta/studies/S000EWGF00000085/recordSummary